Exploring the impact of flexible work arrangements, social support, gender, and job category on the work-life balance of Generation Z workers - Akbar, Ahmad Farhan; Amalia, Ilmi (Universitas Mercu Buana Yogyakarta, 2023)
The work-life balance is the ability of individuals to effectively manage resources such as time and energy across multiple roles within the professional and personal life domain, extending beyond the confines of familial responsibilities. This balance significantly correlates with life satisfaction, job contentment, work dedication, and better mental health. This study aimed to explore the impact of Flexible Work Arrangements, Social Support, Gender, and Job Categories on Generation Z Workers. Conducting a quantitative analysis and using a non-probability sampling method, the study comprised a sample of 258 workers aged between 18 to 28 years residing in Jabodetabek. The Work/Nonwork Interference and Enhancement Scale measuring tool developed by Fisher et.al (2009) was used to evaluate the work-life balance. The evaluation of flexible work arrangements used the assessment tool developed by Hyland (2000), while the measurement of social support used the Multidimensional Scale of Perceived Social Support (MSPSS) by Zimet et al (1988). The validity of the measuring instrument underwent scrutiny through Confirmatory Factor Analysis (CFA), with hypothesis testing conducted via Multiple Regression Technique. The results showed that five independent variables significantly influence the work-life balance, namely the use of adaptability, the availability of flexibility, preference for resilience, family support, and gender. However, variables such as aid from friends, significant other support, and job category are not significant in this context. Keyword: Work-life balance, generation z, flexible work